Keeping kids in school: modelling school-based testing and quarantine strategies during the COVID-19 pandemic in Australia - Abeysuriya, Romesh G.; Sacks-Davis, Rachel; Heath, Katherine; Delport, Dominic; Russell, Fiona M.; Danchin, Margie; Hellard, Margaret; McVernon, Jodie; Scott, Nick (Frontiers in Public Health, 2023)
Background: In 2021, the Australian Government Department of Health commissioned a consortium of modelling groups to generate evidence assisting the transition from a goal of no community COVID-19 transmission to ‘living with COVID-19’, with adverse health and social consequences limited by vaccination and other measures. Due to the extended school closures over 2020-21, maximising face-to-face teaching was a major objective during this transition. The consortium was tasked with informing school surveillance and contact management strategies to minimise infections and support this goal. Methods: Outcomes considered were infections and days of face-to-face teaching lost in the 45 days following an outbreak within an otherwise COVID-naïve school setting. A stochastic agent-based model of COVID-19 transmission was used to evaluate a ‘test-to-stay’ strategy using daily rapid antigen tests (RATs) for close contacts of a case for seven days compared with home quarantine; and an asymptomatic surveillance strategy involving twice-weekly screening of all students and/or teachers using RATs. Findings: Test-to-stay had similar effectiveness for reducing school infections as extended home quarantine, without the associated days of face-to-face teaching lost. Asymptomatic screening was beneficial in reducing both infections and days of face-to-face teaching lost and was most beneficial when community prevalence was high. Interpretation: Use of RATs in school settings for surveillance and contact management can help to maximise face-to-face teaching and minimise outbreaks. This evidence supported the implementation of surveillance testing in schools in several Australian jurisdictions from January 2022.